Sonographic assessment of renal growth in patients with Beckwith-Wiedemann syndrome: the Beckwith-Wiedemann syndrome renal nomogram - Clara L Ortiz-Neira (Clinics, 2009)
BACKGROUND: Beckwith-Wiedemann syndrome is a disorder of somatic overgrowth. Evidence of kidney overgrowth is a diagnostic criterion that may be used to help identify those patients who are at the greatest risk of developing Wilms tumors. In such subjects, kidney size is typically larger than that of age-matched normal controls. OBJECTIVE: The purpose of our study was to generate a nomogram that could be used to measure renal dimensions in children with Beckwith-Wiedemann syndrome in a clinical setting. MATERIALS & METHODS: All of the Beckwith-Wiedemann syndrome patients followed at our institution from 1996 to 2004 were eligible for inclusion in our study. Renal length was measured with a curvilinear transducer and with the patient supine. Renal lengths were measured for both kidneys using real-time ultrasound for all patients. Their data were compared with those of age-matched controls reported in the 1984 study by Rosenbaum et al. RESULTS: Ninety-six children with Beckwith-Wiedemann syndrome were followed from 1996 to 2004. Forty-three of these patients met our criteria for inclusion in the study: 28 girls (65%) and 15 boys (35%). We identified a linear relationship between kidney length and patient age. No statistically significant differences in renal length were found between boys and girls (p=0.2153) or between the kidneys on either side of the body (p=0.9613). CONCLUSION: Our study provides a practical, simple renal growth chart that offers a reasonable, sensitive method for evaluating kidney size in children with Beckwith-Wiedemann syndrome.